BEST PRACTICE PENERAPAN BLENDED E-LEARNING BERBASIS SISWA PADA PEMBELAJARAN BAHASA INGGRIS DI SMK NEGERI 1 JUWIRING - ABDUL AZIS (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This best practice aims to facilitate distance learning (online), make learning more interactive and fun, encourage students to “run” (Learn fluently independently). Independent Fluency Learning (BERLARI) is carried out through several stages, namely preparation, implementation and evaluation. Learning English which was developed with the concept of